Violência e relações de gênero : vivências de mulheres de uma casa-abrigo - Winck, Gustavo Espíndola (2017)
The present thesis is composed of studies that aim to discuss and problematize violence and gender relations, from the experiences of women in a shelter house. These participants were both women in situations of violence, sheltered in the institution, and its multidisciplinar team of professionals, called "caregivers". The writing is based on being able to make possible the reflection and the approach of questions related to gender in our reality, historically, socially and culturally ruled by the production and reproduction of inequities of power, as well as by mechanisms of women’s oppression. Objective: To discuss perceptions about violence and gender relations from the perspectives of women victims of violence and their caregivers, as well as to address data that characterize the shelter functioning, as part of the serious social problem constituted by the different forms of violence against women in our country. Method: Three studies were carried out to compose this thesis, all conceived in a transverse descriptive observational design, and within a qualitative-descriptive lineation scope. The first one was elaborated from individual interviews with women who were victims of violence, based on the precepts of the Narrative Interview, and analyzed according to the assumptions of the Discourse Analysis. The second study was based on interviews with caregivers, both individually and in a thinking-based group. In order to do so, the assumptions of the Semi- Structured Interview were adopted in order to guide the collection process more specificially, and the data were again treated from the Discourse Analysis method. Finally, the third study is characterized by a data survey based on the attendances provided by the shelter-house between 2006 and 2013, discussing how they were characterized after the implementation of 11.340/06 Law, better known as "Maria da Penha Law". Results: It was possible, through the studies carried out, to discuss how perceptions about violence and gender relations, both on women in situations of violence and on their caregivers, can represent the gender signification modes that historically command our society, as well as to consider the work of shelterhouses as essential elements for a social support network aimed at disrupting and preventing gender-based violence.